Innovative Approaches to Natural Killer Cell Engineering: Overcoming Challenges in CRISPR-Cas9 Genome Editing, Transgene Expression, and Cryopreservation - Jo, Dong-Hyeon (Université d'Ottawa / University of Ottawa, 2025)
Natural killer (NK) cells, crucial players in the innate immune system, hold immense potential for cancer immunotherapy due to their ability to target malignant cells without prior antigen sensitization and their low risk of adverse effects such as graft-versus-host disease (GvHD), cytokine release syndrome (CRS), and neurotoxicity. Despite these advantages, challenges such as suboptimal gene-editing techniques, transgene silencing, and cryopreservation-induced dysfunctions have hindered their clinical application. Here, I addressed these hurdles by integrating innovative approaches: a one-step CRISPR-Cas9-mediated gene knockout paired with therapeutic genes such as chimeric antigen receptor (CAR) and interleukin (IL)-15 transgenesis, achieving simultaneously modified NK cell populations. To counteract transgene silencing, histone deacetylase inhibitors (HDACis) were employed, resulting in sustained CAR expression and enhanced anti-tumor efficacy against multiple myeloma in vitro and in vivo. Furthermore, optimized cryopreservation protocols implemented during the early expansion phase significantly improved NK cell recovery, viability, and versatility for therapeutic applications. By integrating advanced genetic engineering, epigenetic modulation, and optimized cryopreservation strategies, my thesis establishes a scalable and durable foundation for effective NK cell-based immunotherapies to treat a wide range of cancers.
Keywords: Natural killer cells; Immune cell engineering; Chimeric antigen receptor; CRISPR-Cas9; Viral particle engineering; Cryopreservation; Transgene stability; Histone deacetylase inhibitors